Preliminary assessment of the role of mangrove species in the control of heavy metals in oil production waters. - Grosso, Jorge Luis; Restrepo, Ricardo; Sanchéz, Luz Esther; Avendaño, Dario; Mantilla, I. (CT&F - Ciencia, Tecnología y Futuro, 1996)
Tree species of Mangrove were planted in an oil production flooded water area in order to study their efficiency as biological filters for controlling heavy metals in the water. The results indicate that the plants not only successfully adapted to the continental environment but also serve as excellent biological filters accumulating barium and chromium in their structure. This process allowed for a richer and renewed biological diversity in the area which favored the reappearance of vegetal and animal species that had disappeared from the ecosystem. Based on the quantification of the metals accumulated by plants, it was found that these metals accumulate in different parts of the plant depending on the plant species regardless of the physicochemical characteristic of the water and the weather conditions. The plants accumulated up to 200 gm-3 of barium in their root and stem. The Rizophora mangle species accumulated the greatest amounts of barium and Avicennia germinans showed the largest survival rates.